2022
DOI: 10.1007/s11356-022-22772-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the influence of foreign direct investment and urbanization on the development of private financial system and its ecological footprint

Abstract: In this research, the objective is to examine how private financial development, urbanization and foreign direct investment and economic growth affects the environment using the ecological footprint as an indicator. Panel data was used for 100 countries from 1980 to 2019, classified according to their income level. Several econometric steps were used to estimate the results, such as cointegration and causality techniques. The results show that the private financial system and environmental degradation have a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 87 publications
3
11
0
Order By: Relevance
“…2023; Udemba, 2021;Ponce et al 2023). CE and FDI also move in opposite direction as per the results of the study.…”
supporting
confidence: 63%
“…2023; Udemba, 2021;Ponce et al 2023). CE and FDI also move in opposite direction as per the results of the study.…”
supporting
confidence: 63%
“…Considering the availability of the data provided by the global ecological footprint, which is limited to 2018, the research therefore selects a period of twenty years. Researchers often incorporate the ecological footprint metric into their studies based on data availability, aligning it with other factors in terms of temporal congruence, ensuring that the timeframes of these variables are synchronized with the 'Ecological footprint' dependent variable (Ponce et al 2023;Kibria, 2023;Uzar & Eyuboglu, 2023). The comprehensive variable (Main variable) used to measure the global ecological footprint stands for the level of ecological footprint that human actions have on the environment Kihombo et al, 2021).…”
Section: Methodology Of the Studymentioning
confidence: 99%
“…The study of Abdouli and Hammami [84] showed, by applying the VAR model, that there is a one-way causal relationship between environmental quality and FDI for 17 countries in the MENA region. When analyzing panel data for 100 countries from 1980 to 2019, Ponce et al [85] found that FDI has a unidirectional effect on environmental deterioration in high-income countries. The research of Lan et al [58] investigates the link between human capital, FDI, and environmental emissions.…”
Section: The Foreign Capital Investment Inflow Effects On Environment...mentioning
confidence: 99%